Bovine preimplantation embryos with silenced nucleophosmin mRNA are able to develop until the blastocyst stage - Toralova, Tereza; Benesova, Veronika; Kepkova, Katerina Vodickova; Vodicka, Petr; Susor, Andrej; Kanka, Jiri (Reproduction (Cambridge, England), 2012)
This study was conducted to investigate the effect of silencing nucleophosmin in the development of in vitro-produced bovine embryos. Nucleophosmin is an abundant multifunctional nucleolar phosphoprotein that participates, for example, in ribosome biogenesis or centrosome duplication control. We showed that although the transcription of embryonic nucleophosmin started already at late eight-cell stage, maternal protein was stored throughout the whole preimplantation development and was sufficient for the progression to the blastocyst stage. At the beginning of embryogenesis, translation occurs on maternally derived ribosomes, the functionally active nucleoli emerge during the fourth cell cycle in bovines. We found that nucleophosmin localisation reflected the nucleolar formation during bovine preimplantation development. The protein was detectable from the beginning of embryonic development. Before embryonic genome activation, it was dispersed throughout the nucleoplasm. The typical nucleolar localisation emerged with the formation of active nucleoli. At the blastocyst stage, nucleophosmin tended to localise especially to the trophectoderm. To see for how long is maternal nucleophosmin preserved, we silenced the nucleophosmin mRNA using RNA interference approach. Although a large portion of nucleophosmin was degraded in embryos with silenced nucleophosmin mRNA, an amount sufficient for normal development was preserved and we detected only a temporal delay in nucleophosmin relocalisation to nucleoli. Moreover, we observed no defects in nuclear shape or cytoskeleton previously found in somatic cells and only a non-significant decrease in embryonic developmental competence. Thus, our results show that the preserved amount of maternal nucleophosmin is sufficient for preimplantation development of bovine embryo.